قياس الطاقة غير المستغلة باستخدام نظام التكاليف على أساس الأنشطة الموجه بالوقت(td-abc) -دراسة تطبيقية بمؤسسة مطاحن الجنوب "gmsud" ببلدية أوماش- ولاية بسكرة- - سوداني, زكرياء; تومي, ابراهيم (جامعة الوادي - University of Eloued, 2023)
This study aims to reveal the volume of untapped energy in the Great Mills Corporation of the South "GMsud" by applying the time-driven activity-based costing system (TD-ABC), and in order to answer the problem of this study, the analytical descriptive approach was relied on and a case study tool, and concluded The study aimed to determine the size of the unutilized energy in the "GMsud" institution by 62,82℅ which would assist the managers in resource planning and optimal utilization of them, in addition to that the application of the (TD-ABC) system improves the quality of information related to costs in a more accurate and local way. The traditional system applied in the institution that will rationalize expenditures and achieve greater accuracy in allocating indirect burdens
MillsMeasurement of idle energy using time-driven activity-based costing (TD-ABC) An applied study at the Southern municipality of Oumache - Biskra Province - Corporation “GMsud” i
مقال
Keywords: نظام التكاليف على أساس الأنشطة (TD-ABC) ; الطاقة غير المستغلة ; أعباء غير المباشرة: time-driven activity-based costing system (TD-ABC)، Untapped energyࢫ،indirect costs